MANAGEMENT OF EARLY CHILD’S CHARACTER DEVELOPMENT THROUGH HABITUATION AND EXEMPLARY IN KINDERGARTEN - Sofiana Utami; Abdul Wafi (re-JIEM (Research Journal of Islamic Education Management), 2020)
The four problems that become the main study in this study. First, how to plan early child’s character development through habituation and exemplary in the Kindergarten of Al-Quran Matsaratul Huda Panempan Pamekasan. Second, how to organize the development of early child’s character through habituation and exemplary in the kindergarten of Al-Quran Matsaratul Huda Panempan Pamekasan. Third, how the implementation of early child’s character development through habituation and exemplary in the kindergarten of Al-Quran Matsaratul Huda Panempan Pamekasan. Fourth, how to evaluate the character development of the early child through habituation and examplary in the kindergarten of Al-Quran Matsaratul Huda Panempan Pamekasan. It is a qualitative descriptive study where the data collected through field observation, interviews, and documentation. The results showed that developing an early child’s character should be well managed. Instilling good habituation for the children and becoming an excellent example of the teachers proved successful in early child’s character development.